Isolation and Characterization of Antihyperglycaemic Triterpenes from the Flowers of Calotropis gigantea - Naveen K. Choudhary (Journal of Global Pharma Technology, 2018)
Calotropis gigantea, Akda, belonging to family Asclepidaceae, is a medicinal plant distributed widely throughout the India. In our previous study, chloroform extract of Calotropis gigantean showed potent anti-diabetic activity. Hence our main aim is to isolate the active compounds present in chloroform extract which might be responsible for anti-diabetic activity. Bioactivity guided isolation was performed to isolate the active compounds. Three phytoconstituents, β-sitosterol, Stigmasterol and α- amyrene have been isolated from the flowers of Calotropis gigantea. The structures of these phytoconstituents have been established by spectroscopic methods.Keywords: Calotropis gigantea, β-sitosterol, Asclepidaceae, chloroform extract, anti-diabetic activity.